Cost comparison of commonly used antidepressant drugs with drug price control order in India - Kumar, Narendra; Abbas, Alisha; Ahmad, Akhlaque; Choudhary, Reshma; Ganguly, Arpan; Dixit, Rakesh Kumar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Price of a drug is an important factor for compliance to the treatment. So, to overcome the high prices of drugs, National Pharmaceutical Pricing Authority (NPPA) under government of India has issued Drug Price Control Order (DPCO) list containing commonly used drugs. Pharmaceutical companies can be punished if they keep their prices higher than the ceiling price mentioned in the DPCO. To find out the price variations of commonly used antidepressant drugs included in DPCO list of 29th April 2019. Methods: A list of all oral antidepressant drugs included in DPCO of 29th April 2019 and available in Indian market was procured from medguide India. Analysis of number of total brands following as well as not following DPCO ceiling price was done. Results: Author found 17 formulations of four antidepressant drugs included in DPCO. Total 556 brands found out of which 84.6% were following the DPCO and 15.4% of brands prices were higher than the ceiling price of DPCO. Conclusions: Though large number of companies are following the DPCO but still strict regulation is needed to further increase the compliance of guidelines.